2010
DOI: 10.1038/onc.2010.42
|View full text |Cite
|
Sign up to set email alerts
|

Induced G1 cell-cycle arrest controls replication-dependent histone mRNA 3′ end processing through p21, NPAT and CDK9

Abstract: Proper cell cycle-dependent expression of replicationdependent histones is essential for packaging of DNA into chromatin during replication. We previously showed that cyclin-dependent kinase-9 (CDK9) controls histone H2B monoubiquitination (H2Bub1) to direct the recruitment of specific mRNA 3 0 end processing proteins to replicationdependent histone genes and promote proper pre-mRNA 3 0 end processing. We now show that p53 decreases the expression of the histone-specific transcriptional regulator Nuclear Prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
63
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(65 citation statements)
references
References 37 publications
1
63
0
Order By: Relevance
“…A similar accumulation of read-through transcripts has previously been described after the depletion of several other factors important for histone RNA processing (22)(23)(24)(25). In agreement with these previous studies, we could show that the majority of free RNA is present in earlier fractions and ribosomes and polysomes in later fractions.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…A similar accumulation of read-through transcripts has previously been described after the depletion of several other factors important for histone RNA processing (22)(23)(24)(25). In agreement with these previous studies, we could show that the majority of free RNA is present in earlier fractions and ribosomes and polysomes in later fractions.…”
Section: Discussionsupporting
confidence: 92%
“…2E), we wanted to characterize their nature, metabolism, and potential function. Several reports suggested that upon misprocessing, replicationdependent histone transcripts acquire a poly(A) tail (22)(23)(24)(25). Indeed, we found by in silico analysis that several members of the human replication-dependent histone genes contain cryptic polyadenylation signals downstream of the canonical cleavage sites.…”
Section: Resultsmentioning
confidence: 75%
See 2 more Smart Citations
“…It negatively regulates the G1/S phase transition and its up-regulation results in cell cycle arrest in G1 phase (20). In association with CDK2 complexes, it inhibits kinase activity and blocks cell cycle progression through G1/S arrest (21).…”
Section: Discussionmentioning
confidence: 99%